Appinite suites and their genetic relationship with coeval voluminous granitoid batholiths. Issue 6 (12th April 2020) - Murphy, J. Brendan
ABSTRACT: Appinite complexes preserve evidence of mantle processes that produce voluminous granitoid batholiths. These plutonic complexes range from ultramafic to felsic in composition, deep to shallow emplacement, and from Neo-Archean to Recent in age. Appinites are a textural family characterized by idiomorphic hornblende in all lithologies, and spectacular textures including coarse-grained mafic pegmatites, fine-grained 'salt-and-pepper' gabbros, as well as planar and linear fabrics. Magmas are bimodal (mafic-felsic) in composition; ultramafic rocks are cumulates, intermediate rocks are hybrids. Their geochemistry is profoundly influenced by a mantle wedge extensively metasomatized by fluids/magmas produced by subduction. Melting of spinel peridotite sub-continental lithospheric mantle (SCLM) produces appinites whose geochemistry is indistinguishable from coeval low-K calc-alkalic arc magmatism. Coeval felsic rocks within appinite complexes and adjacent granitoid batholiths are crustal magmas. When subduction terminates, asthenospheric upwelling (e.g. in a slab window, or in the aftermath of slab failure) induces melting of metasomatized garnet SCLM to produce K-rich sho shonitic magmas enriched in large ionic lithophile and light relative to heavy rare earth elements, whose asthenospheric component can be identified by Sm-Nd isotopic signatures. Coeval late-stage Ba-Sr granitoid magmas have a 'slab failure' geochemistry, resemble TTG and adakitic suites, and are formed either by fractionation of an enriched (shoshonitic) mafic magma, or high pressure melting of a meta-basaltic protolith either at the base of the crust or along the upper portion of the subducted slab. Appinite complexes may be the crustal representation of mafic magma that underplated the crust for the duration of arc magmatism. They were preferentially emplaced along fault zones around the periphery of the granitoid batholiths (where their ascent is not blocked by overlying felsic magma), and as enclaves within granitoid batholiths. When subduction ceases, appinite complexes with a more pronounced asthenospheric component are preferentially emplaced along active faults that bound the periphery of the batholiths.